KEBERDAYAAAN PETANI MELALUI ADMINISTRASI KELOMPOKTANI PADA BUDIDAYA PADI (ORYZA SATIVA L.) DI KECAMATAN JATIBARANG KABUPATEN INDRAMAYU - Sarinah Patonah Ningsih; Wida Pradiana; Wasrob Nasruddin (Jurnal Inovasi Penelitian, 2020)
Farmer groups are needed roles in various agricultural activities that have a relationship between farming and socioeconomic activities. Increased farmer group development is directed at the implementation of the agribusiness system, increasing the role, participation of farmers and other rural community members by fostering cooperation between farmers and other parties who have a connection in the development of farming carried out. But besides that farmers are still less concerned about completeness and importance the preparation of administration in groups of farmers. In this study carried out from March to July 2020 in the village of Lobener Lor, Jatibarang District, Indramayu Regency. Study sample, totaling 30 members of the tami group by using the quota sampling method. The variables contained in this study are farmer characteristics, external support and the level of empowerment. Data analysis using descriptive analysis, Spearman rank correlation, and Kendall's W. The results of the study indicate that empowerment is included in the medium category. Related factors are the level of education and land area. Whereas for external support that includes the availability of facilities and infrastructure and support from farmer groups. The strategy to increase the empowerment of farmers through the administration of farmer groups in rice farming which must be improved is an indicator of the level of farmer administration capacity. The parameter that must be improved is the administration of activities.